China's energy economy: A survey of the literature - Ma, H.; Oxley, Leslie; Gibson, J. (2010)
This paper reviews the literature on China's energy economy, focusing particularly on: (i) the relationship between energy consumption and economic growth; (ii) China's changing energy intensity; (iii) energy demand and energy-non-energy substitution; (iv) the emergence of energy markets in China; and (v) economic reforms in the energy industry. After reviewing the literature, the paper presents the main findings that some important issues remain unanswered, for example, what determines energy consumption behavior; the effects of substitution of and demand for energy; and technological change effects on energy intensity. Finally, the review suggests some topics worthy of future study. © 2010 Elsevier B.V. All rights reserved.